Modernization of Tax Administration Through The Implementation of Tapping Boxes In An Effort To Optimize Tax Compliance - Khy'sh Nusri Leapatra Chamalinda; Intan Putri Rismadhani (Jurnal Pajak dan Keuangan Negara (PKN), 2024)
The presence of modernization of tax administration to improve services and increase tax compliance. This study aims to explore the implementation of the tapping box application in an effort to optimize tax compliance and local revenue in Bangkalan Regency. Descriptive qualitative research method with a case study approach. Data collection techniques with observation, interviews, and documentation. The data validity test uses source triangulation, which then analyzes the data and draws conclusions. The results showed that the implementation of the taping box was good enough. The implementation of the tapping box seeks to optimize taxpayer compliance, as evidenced by the fact that almost 71% of hotel and restaurant taxpayers have used the tapping box. However, in terms of realization of hotel and restaurant tax revenues, it has not reached the target. Challenges and obstacles in implementing tapping box often occur. Bapenda Bangkalan's strategy in dealing with these obstacles is to communicate and socialize, impose sanctions on taxpayers who do not comply with the rules, and cooperate with tapping box technicians. The cooperation of the government, taxpayers and the community is needed to optimize the implementation of tax administration modernization which is expected to increase tax compliance and tax revenue.